Construction of solvent-resistant interphase of CF/PEEK composites via introducing water-based crosslinkable polyaryl ether sizing agent. (7th July 2022) - Liu, Liu; Hu, Jiaoli; Zhao, Lianshuang; Liu, Yu; Yan, Fei; Ao, Yuhui
Abstract: Carbon fiber (CF) reinforced polyether ether ketone (PEEK) occupied an important position in composites due to its excellent properties. However, the weak interfacial strength became a bottleneck restricting the further development. In this work, water-based crosslinkable polyarylether sizing agent with different concentrations were prepared. These sizing agents have good storage stability, with particle sizes ranging from 54.6 nm to 78.5 nm. The chemical bonds formed by self-crosslinking reaction of nitrile groups during the hot-pressing process endowed the sizing agent with outstanding solvent resistance. In addition, the glass transition temperature of the crosslinked sizing agent was increased to 285.5 °C. The maximum bending strength and interlaminar shear strength of CF1.5/PEEK composites were 43.1% and 42.7% higher than unsized CF composites. Furthermore, it retained excellent mechanical properties after solvent treatment, owing to the construction of the solvent-resistant interphase. This "thermoplastic processing, thermosetting application" polyarylether sizing agent is expected to further expand the application range of CF/PEEK composites. Graphical abstract: Image 1 Highlights: The "thermoplastic processing, thermosetting application" sizing agent was prepared. The sizing agent with good storage stability and can self-crosslink when heated. Composites possess excellent solvent resistance due to the crosslinkable interphase. This work broaden the application range of CF/PEEK composites under harsh conditions.